Autophagy and hypoxia in colonic adenomas related to aggressive features. - Giatromanolaki, A; Koukourakis, M; Koutsopoulos, A; Harris, A; Gatter, K; Sivridis, E (2013)
AIM: The study investigated whether autophagic activity and hypoxia parallel the adenoma-carcinoma sequence. METHOD: The study comprised 120 tubular adenomas with high-grade dysplasia, including 22 with questionable evidence of invasion, 37 with definite stromal invasion and 29 with severely dysplastic adenoma, 10 traditional serrated adenomas and 22 classical tubular adenomas lacking aggressive features. The samples were stained immunohistochemically for autophagy (LC3A and Beclin-1) and hypoxia-inducible factor1-alpha (HIF1α) markers. RESULTS: LC3A was detected as diffuse cytoplasmic staining and as dense "stone-like" structures (SLS) within cytoplasmic vacuoles. Beclin-1 reactivity was purely cytoplasmic, whereas that of HIF1α was both cytoplasmic and nuclear. SLS counts in noninvasive, nontransformed areas of tubular adenomas were consistently low (median SLS = 0.5; 200× magnification), whereas a progressive increase was noted from areas of equivocal invasion (median SLS = 1.3; 200× magnification) and intramucosal carcinoma (median SLS = 1.4; 200× magnification) to unequivocal invasive foci (median SLS = 2.1; 200× magnification) (P < 0.0001). A similar association was shown for Beclin-1 and HIF1α expression (P < 0.05). Traditional serrated adenomas yielded low SLS counts and weak HIF1α reactivity, but high cytoplasmic LC3A and Beclin-1 expression (P < 0.01). CONCLUSION: A hypoxia-driven autophagy in adenomatous polyps, when particularly intense and localized, is commonly associated with early invasion or severely dysplastic adenoma.